OPTIMALISASI DATA LANDSAT 8 UNTUK PEMETAAN DAERAH RAWAN BANJIR DENGAN NDVI dan NDWI ( Studi Kasus : Kota Bengkulu ) - Aan Erlansari; Boko Susilo; Franky Hernoza (Engineering Faculty Universitas Lampung, 2020)
Indonesia is classified as a tropical region with rainfall data ranging from medium to high. This has become one of the causes of frequent flooding. Bengkulu which is one of the provinces in Indonesia, has a topography that is at an elevation of 0-16 meters above sea level with 70% flat topography and 30% small hilly. Swamp area dominates the lowlands so that it cannot optimally absorb water into the soil. This study identifies areas with potential flooding using data obtained through Landsat 8 and processes them using the NDVI and NDWI methods. NDVI detected and classified a map into five classifications; dry land with red colour, scarce vegetation with yellow pigment, sparse vegetation with soft green colour, solid vegetation with a dark green colour. Meanwhile, NDWI classified into 3 categories; medium wetness with a brown colour, dry land with beige colour and high wet area with a blue colour.